Prognostic significance of medical therapy in patients with heart failure with reduced ejection fraction - Kocabas, Umut; Ergin, Isil; Kivrak, Tarik; Oztekin, Guelsuem Meral Yilmaz; Tanik, Veysel Ozan; Ozdemir, Ibrahim; Ozcalik, Emre (Wiley Periodicals, Inc, 2023)
Aims The use of guideline-directed medical therapy (GDMT) among patients with heart failure (HF) with reduced ejection fraction (HFrEF) remains suboptimal. The SMYRNA study aims to identify the clinical factors for the non-use of GDMT and to determine the prognostic significance of GDMT in patients with HFrEF in a real-life setting.Methods and results The SMYRNA study is a prospective, multicentre, and observational study that included outpatients with HFrEF. Patients were divided into three groups according to the status of GDMT at the time of enrolment: (i) patients receiving all classes of HF medications including renin-angiotensin system (RAS) inhibitors, beta-blockers, and mineralocorticoid receptor antagonists (MRAs); (ii) patients receiving any two classes of HF medications (RAS inhibitors and beta-blockers, or RAS inhibitors and MRAs, or beta-blockers and MRAs); and (iii) either patients receiving class of HF medications (only one therapy) or patients not receiving any class of HF medications. The primary outcome was a composite of hospitalization for HF or cardiovascular death. The study population consisted of 1062 patients with HFrEF, predominantly men (69.1%), with a median age of 68 (range: 20-96) years. RAS inhibitors, beta-blockers, and MRAs were prescribed in 76.0%, 89.4%, and 55.1% of the patients, respectively. The proportions of patients receiving target doses of guideline-directed medications were 24.4% for RAS inhibitors, 11.0% for beta-blockers, and 11.1% for MRAs. Overall, 491 patients (46.2%) were treated with triple therapy, 353 patients (33.2%) were treated with any two classes of HF medications, and 218 patients (20.6%) were receiving only one class of HF medication or not receiving any HF medication. Patient-related factors comprising older age, New York Heart Association functional class, rural living, presence of hypertension, and history of myocardial infarction were independently associated with the use or non-use of GDMT. During the median 24-month period, the primary composite endpoint occurred in 362 patients (34.1%), and 177 of 1062 (16.7%) patients died. Patients treated with two or three classes of HF medications had a decreased risk of hospitalization for HF or cardiovascular death compared with those patients receiving <= 1 class of HF medication [hazard ratio (HR): 0.65; 95% confidence interval (CI): 0.49-0.85; P = 0.002, and HR: 0.61; 95% CI: 0.47-0.79; P < 0.001, respectively].Conclusions The real-life SMYRNA study provided comprehensive data about the clinical factors associated with the non-use of GDMT and showed that suboptimal GDMT is associated with an increased risk of hospitalization for HF or cardiovascular death in patients with HFrEF.
Keywords: Guideline-directed medical therapy; Heart failure; Hospitalization; Mortality